PENGARUH IKLIM ORGANISASI TERHADAP PRODUKTIVITAS KERJA DI UNIT PELAKSANA TEKNIS KURIKULUM KECAMATAN JASINGA KABUPATEN BOGOR - Karyana, Ayi (Jurnal Organisasi dan Manajemen, 2012)
The research analyzed the influence of organizational climate dimension on the work productivity at the Local Technical Service Unit (UPTK) for Pre-Elementary and Elementary Education in the Jasinga Sub District of Bogor District. The research used explanatory survey method. Purposive sampling was the technique used to obtained samples. Data were collected by means of questionnaires, interviews and observations. The questionnaires were given to 75 people at the UPTK and they were all returned. The method used to analyze the data is path analysis. Statistical result showed that the variable dimension of the organizational climate has positive and significant impact on the productivity. The UPTK in the Jasinga Sub District of Bogor was totality consistent in giving meaning to the nature of conducive organizational climate. But in order to increase the effectivity and efficiency of the work productivity, it is necessary to socialize the organizations vision and mission, to increase the intensity of the communication, to share responsibility on everybody, to motivate the human resource involved in the job, to encourage reward and punishment, and to provide technological facilities needed to support the organization. Penelitian ini menganalisis pengaruh dimensi iklim organisasi terhadap produktivitas kerja di Unit Pelaksana Teknis Kurikulum (UPTK) Kecamatan Jasinga Kabupaten Bogor. Metode penelitian yang digunakan adalah metode survei eksplanatori. Teknik sampling yang digunakan adalah purposive sampling dengan pertimbangan dan bertujuan tertentu. Prosedur pengumpulan data dilakukan dengan penyebaran angket, wawancara dan observasi. Angket disebarkan kepada 75 orang pada UPTK Kecamatan Jasinga, dan angket kembali semuanya. Metode analisis data yang digunakan penulis adalah analisis jalur. Hasil pengujian statistik menunjukkan bahwa dimensi variabel iklim organisasi berpengaruh positif dan signifikan terhadap produktivitas kerja. UPTK Kecamatan Jasinga Kabupaten Bogor secara total konsisten dalam memberikan pemaknaan terhadap hakikat iklim organisasi yang kondusif terhadap organisasinya. Tetapi untuk lebih meningkatkan efektivitas dan efisiensi produktivitas kerja dipandang perlu untuk mensosialisasikan visi dan misi organisasi, meningkatkan intensitas arus komunikasi, menanamkan tanggung jawab, memotivasi sumber daya manusia yang terlibat dalam pekerjaan, menegakkan sistem imbalan dan sanksi dan melengkapi sarana prasarana teknologi yang diperlukan untuk mendukung organisasi.